2014
DOI: 10.1002/jso.23577
|View full text |Cite
|
Sign up to set email alerts
|

Tracheobronchial injury in the setting of an esophagectomy for cancer: Postoperative discovery a bad omen

Abstract: Patients with proximal tumors and radiation administration as a component of neoadjuvant treatment are more likely to suffer a tracheobronchial injury. An aggressive reoperative approach is warranted in patients with injuries that are discovered postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Radiotherapy to the neck region for example might be associated with an increased risk of wound complications after head and neck surgery, 12,25 increased adhesions with more difficult dissection of the esophagus 3 and higher rates of intraoperative tracheobronchial injury. 4,26 Most importantly, a number of studies suggested that radiotherapy leads to increased interstitial fibrosis and congestion of the lungs, 27 and decreased irradiated lung volume might influence and increase the risk of postoperative complications. [28][29][30] Our study presents some limitations that have to be considered for proper interpretation of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy to the neck region for example might be associated with an increased risk of wound complications after head and neck surgery, 12,25 increased adhesions with more difficult dissection of the esophagus 3 and higher rates of intraoperative tracheobronchial injury. 4,26 Most importantly, a number of studies suggested that radiotherapy leads to increased interstitial fibrosis and congestion of the lungs, 27 and decreased irradiated lung volume might influence and increase the risk of postoperative complications. [28][29][30] Our study presents some limitations that have to be considered for proper interpretation of our results.…”
Section: Discussionmentioning
confidence: 99%
“…The median time between esophagectomy and surgical repair of PETEF was 61 days (range, 7 days to 28 years). Anastomotic leak or gastric conduit necrosis was responsible for PETEF in 6 patients (54.5%), whereas other causes were erosion of a tracheal appliance (n [ 2), gastric conduit staple line erosion (n [ 1), anastomotic stricture dilation (n [ 1), and recurrent esophageal cancer (n [ 1). Membranous airway defects were repaired primarily and buttressed with muscle or omental flaps in 8 patients (72.7%), whereas two (18.2%) were repaired with bio-prosthetic patches and one (9.1%) was repaired with a sleeve resection of the bronchus.…”
mentioning
confidence: 99%
“…Multiple risk factors are associated with the occurrence of this uncommon, but potentially fatal complication. In the case presented, repeated double-lumen intubation [2] and sclerotic changes of esophagealtracheal muscle fibers after neoadjuvant chemoradiotherapy for the treatment of advanced middle-third ESCC played a decisive role [1]. Furthermore, the latter condition led to inflammation and local edema, making esophageal dissection and extended mediastinal lymphadenectomy quite difficult to perform [1].…”
Section: Discussionmentioning
confidence: 90%
“…In the case presented, repeated double-lumen intubation [2] and sclerotic changes of esophagealtracheal muscle fibers after neoadjuvant chemoradiotherapy for the treatment of advanced middle-third ESCC played a decisive role [1]. Furthermore, the latter condition led to inflammation and local edema, making esophageal dissection and extended mediastinal lymphadenectomy quite difficult to perform [1]. Given this background, the inevitable traction and the effect of thermal cautery during the dissection may have contributed to the extent of both injuries.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation